Ucieczki za granicę oraz inne formy nielegalnej emigracji w historii Śląska Opolskiego. Część I. Lata 1945–1955. Zarys problematyki w świetle materiałów cywilnego aparatu bezpieczeństwa - Bereszyński, Zbigniew (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The region of Opole Silesia, and from 1950 the Opole Voivodeship (province), encompassed a vast majority of the newly formed Polish–Czechoslovakian borderland, shaped in consequence of World War II. This particular part of the state border was characterized by lack of significant natural barriers.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne